The Role of Endoscopic Retrograde Cholangiopancreatography in the Diagnosis of Biliary Atresia: 14 Years' Experience - Negm, Ahmed A.; Petersen, Claus; Markowski, Andrea; Luettig, Birgit; Ringe, Kristina I.; Lankisch, Tim O.; Manns, Michael P.; Ure, Benno; Schneider, Andrea S. (European Journal of Pediatric Surgery, 2018)
Introduction Biliary atresia (BA) is a rare destructive inflammatory obliterative cholangiopathy of neonates. Early diagnosis is important in disease management. The aim was to evaluate the role of endoscopic retrograde cholangiopancreatography (ERCP) in diagnosing BA in a large cohort. In addition, we evaluated whether parameters such as bile trace, GGT, bilirubin, and laboratory values in combination can be used to develop a risk score that could indicate the referral to specialized centers.Materials and Methods All infants with neonatal cholestasis (2000–2014) who presented to our endoscopy unit for suspected BA were included. Demographics, laboratory parameters, ultrasound findings, liver biopsy results, ERCP diagnosis, and surgical outcome were collected. Value and safety of ERCP and risk factors for BA were retrospectively analyzed.Results We included 251 infants in our cohort (55% males, median age: 53 days). BA was intraoperatively diagnosed in 155 (83.4%) patients and was excluded in 30 (16.2%). Fifty-six cases were not operated due to the ERCP findings. ERCP was successful in 224/251 patients (89.2%) with no procedure-related complications. The operative and endoscopic diagnosis matched in 96.6% of the patients (positive predictive value: 92.2%, negative predictive value: 97.1%). In comparison to cases with excluded BA, the ones with this disease were significantly associated with absence of duodenal bile traces (98.4 vs. 1.6%, p < 0.001), higher bilirubin (p < 0.001, cutoff 7.3 mg/dL), and higher GGT (p < 0.001, cutoff 250 U/L).Conclusion ERCP is safe and accurate in the hands of experts in diagnosing BA if the cause of cholestasis is unclear. While evaluating the role of ERCP for diagnosing this disease, we found that the secondary parameters GGT > 250 U/L, bilirubin > 7.3 mg/dL (125 μmol/L), and the absence of bile traces are risk factors.
Keywords: neonatal cholestasis; pediatric endoscopic retrograde cholangiopancreatography; cholangitis; endoscopic diagnosis; kasai